Paint [videorecording (DVD)] - McAdams, Brit; Wilson, Owen, 1968-; Watkins, Michaela, 1971-; McLendon-Covey, Wendi, 1969-; Ciara Renée, 1990-; Freyer, Lucy; Strus, Lusia; Root, Stephen (IFC Films, 2023)
Carl Nargle, Vermont's #1 public television painter is convinced he has it all: a signature perm, custom van, and fans hanging on his every stroke...until a younger, better artist steals everything (and everyone) Carl loves.